Motywy podejmowania prób samobójczych przez młodzież w wieku 13-19 lat = Motives for suicide attempts by youth aged 13-19 - Gmitrowicz, Agnieszka; Wolanek, Urszula; Madej, Agata; Makara-Studzińska, Marta (Journal of Education, Health and Sport, 2015)
Gmitrowicz Agnieszka, Wolanek Urszula, Madej Agata, Makara-Studzińska Marta. Motywy podejmowania prób samobójczych przez młodzież w wieku 13-19 lat = Motives for suicide attempts by youth aged 13-19. Journal of Education, Health and Sport. 2015;5(6):51-64. ISSN 2391-8306. DOI 10.5281/zenodo.18278 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A51-64 https://pbn.nauka.gov.pl/works/563208 http://dx.doi.org/10.5281/zenodo.18278 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2015. Revised 28.05.2015. Accepted: 04.06.2015. Motywy podejmowania prób samobójczych przez młodzież w wieku 13-19 lat Motives for suicide attempts by youth aged 13-19 Agnieszka Gmitrowicz1, Urszula Wolanek2, Agata Madej3, Marta Makara-Studzińska3 1Klinika Psychiatrii Młodzieżowej CSK IS UM w Łodzi 1Youth Psychiatry Clinic, Central Clinical Hospital, Institute of Dentistry, Medical University of Łódź 2Oddział Psychiatrii Młodzieżowej UM w Łodzi 2Youth Psychiatric Ward, Medical University of Łódź 3Zakład Psychologii Stosowanej UM w Lublinie 3Department of Applied Psychology, Medical University of Lublin Streszczenie Wstęp. Samobójstwo stanowi istotny problem w dziedzinie zdrowia publicznego. Wiek dorastania, nazywany „adolescencją” to najtrudniejszy i najbardziej złożony etap w życiu człowieka. Młodzi ludzie podejmują zachowania dysfunkcyjne będąc pod wpływem takich czynników jak: stres, brak umiejętności życiowych, negatywna presja rówieśnicza. Do najpoważniejszych problemów zdrowotnych wieku młodzieńczego zalicza się: depresję, nieumiejętność radzenia w sytuacjach stresowych, lęk, anoreksję/bulimię, zaburzenia osobowości, nieprzystosowanie społeczne, nadużywanie substancji psychoaktywnych. Zdarzają się momenty, w których ich natężenie staje się silne i prowadzi do przestępstw oraz samobójstw. W literaturze podaje się, iż samobójstwo jest jedną z najczęstszych przyczyn zgonów nastolatków w wieku 15-19 lat. Cel pracy. Określenie motywów podejmowania oraz najczęściej wybieranych metod prób samobójczych (PS) w grupie pacjentów psychiatrycznego oddziału młodzieżowego. Materiał i metoda. W badaniu udział wzięło 80 pacjentów w wieku 13-19 lat. Narzędzie badawcze stanowił kwestionariusz ankiety własnego autorstwa. Uzyskane wyniki poddano analizie procentowej. Wyniki. Najczęstszą metodą targnięcia się na własne życie wśród badanych dziewcząt było przedawkowanie leków (29%) oraz podcięcie żył (9%), natomiast chłopcy jako metodę wybierali powieszenie (6%). Motywy podejmowania PS dotyczyły rozstania z sympatią, kłótni, braku sensu życia, samotności oraz braku wsparcia bliskich. Wnioski. Motywy podejmowania oraz metody działań samobójczych, którymi kierowali się ankietowani zależne były od płci, subiektywnej interpretacji swojej sytuacji życiowej, braku umiejętności w rozwiązywaniu sytuacji trudnych, impulsywności w podejmowanych działaniach oraz braku wsparcia ze strony osób znaczących. Słowa kluczowe: samobójstwo, młodzież, psychiatria, próby samobójcze. Abstract Introduction. Suicide is a major problem in the field of public health. Teen age, called "adolescence", is the most difficult and most complex stage in human life. Young people exhibit dysfunctional behaviour under the influence of different factors, such as stress, lack of social skills, negative peer pressure. The most serious health problems of adolescence include: depression, inability to deal with stressful situations, anxiety, anorexia / bulimia, personality disorders, social maladjustment, psychoactive drugs abuse. There are moments when their intensity becomes so strong that it leads them to delinquencies and suicides. The bibliography states that suicide is one of the most common causes of death of teenagers aged 15-19. Aim of the study. The aim of the study is to determine motives for undertaking and most commonly chosen methods of suicide (MS) in patients of the youth psychiatric ward. Materials and methods. The study involved 80 patients aged 13-19. The research tool was a questionnaire of own authorship. The results were subject to percentage analysis. Results. The most common suicide attempt methods among the surveyed girls were drug overdose (29%) and cut veins (9%), while the boys considered hanging as a method of attempting suicide (6%). The motives for suicide attempt involved breaking up with loved ones, quarrels, lack of meaning in life, loneliness and lack of support of immediate family. Conclusions. Motives for and methods of suicide attempts which the respondents were driven by were dependent on gender, subjective interpretation of one’s situation, lack of skill in dealing with difficult situations, impulsiveness in their actions and lack of support from people important in their lives. Keywords: suicide, youth, psychiatry, suicide attempts.